Punctuality Pattern Among Dental Students - RN, ARUN KISHORE; GANAPATHY, DHANRAJ; SASANKA, KEERTHI (The journal of contemporary issues in business and government, 2020)
Background: Punctuality is a sign of professionalism and helps you to stand as a reliable and trustworthy individual.When a person becomes punctual , everything falls into places , you get discipline in life and also it helps you to reach greater heights . Punctuality is one of the major concerns in the day to day life scenario. The level of punctuality largely influences one's confidence and their attitude. Being Punctual is mainly based on time management and it is the main reason behind success .Time management issue is greatly influenced by perception and behaviour. Materials and Method: The questions were prepared and distributed through an online survey planet link the participants well explained about the study and the results were collected and statistically analysed. Result and discussion: From the analysed results we can see that the majority of the dental students are punctual to their classes and there exists a pattern of punctuality among the students.Conclusion: From the survey, it was evident that majority of the dental students are punctual to their classes and there also exists a punctual pattern among dental college students.